Pengaruh Leverage, Financial Distress, Profitabilitas dan Risiko Ligitasi Terhadap Konservatisme Akuntansi Pada Perusahaan Pertambangan di BEI (2020-2024) - Muazah, Azah Tul; Fajri, Aminul Fajri; Fanani, Baihaqi Fanani (Gorontalo State University, 2026)
The study aimed to assess how leverage, financial distress, profitability, and litigation risk affect accounting conservatism. The independent variables assessed were leverage, financial distress, profitability, and litigation risk, while accounting conservatism functioned as dependent variables. This study examined a total of 81 companies, with samples selected through purposive sampling techniques. In the end, 45 mining businesses that were listed between 2020- 2024 on the Indonesia Stock Exchange made up the sample. Multiple linear regression analysis was performed using SPSS software as part of a quantitative strategy that relied on secondary data. The results demonstrate that while accounting conservatism is positively impacted by profitability, it is not impacted by leverage, financial difficulty, or litigation risk. These findings offer valuable insights into the factors that shape conservative accounting approaches in the mining sector.